Role of oral iron treatment in the management of severe dilated cardiomyopathy in an 18-month-old toddler: a case report - Tamer, Reyhan; Torun, Zeynep; Yozgat, Can Yılmaz; Kuş, Hazar Doğuş; Talebazadeh, Faraz; Tahaoǧlu, Irmak; Uzuner, Selçuk; Yozgat, Yılmaz; Torun, Emel (My University, 2025)
...
Rolle der oralen eisenbehandlung bei der behandlung schwerer dilatativer kardiomyopathie bei einem 18 monate alten kleinkind: ein fallbericht
Keywords: Iron Deficiency Anemia; Toddler; Dilated Cardiomyopathy